Terahertz Radiation Emission from A Surface Wave Pumped Free Electron Laser (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
We develop an analytical formalism for tunable coherent terahertz (THz) radiation generation from bunched relativistic electron beam (REB) counter -propagating to the surface wave in the vacuum region Compton backscatters the surface wave. Plasma supports the surface wave that acquires a large wave number around pump wave frequency. The surface wave extends into vacuum region that can be employed as a wiggler for the generation of terahertz radiation. As the beam bunches pass through the surface plasma wave wiggler, they acquire a transverse velocity, constituting a transverse current producing coherent THz radiation. It was found that the terahertz power increases with electric field as well as with the thermal velocity of electrons. It was also found that the growth rate and efficiency of the instability both increases with the modulation index of the density modulated beam.
Keywords: Terahertz radiation; FEL; SPW; Density modulation